GaAs integrated quantum photonics: Towards compact and multi‐functional quantum photonic integrated circuits (Laser Photonics Rev. 10(6)/2016). Issue 6 (November 2016) - Dietrich, Christof P.; Fiore, Andrea; Thompson, Mark G.; Kamp, Martin; Höfling, Sven
Abstract : Progress in the field of integrated quantum optics has set the stage for the development of an integrated platform for quantum information processing with photons. For the GaAs system, all key functionalities, including single‐photon sources and detectors, photon‐number‐resolving detectors, integrated autocorrelators and tunable Mach‐Zehnder‐interferometers have already been realized and tested. This lays the foundation for a fully‐integrated quantum photonic technology, with potential applications in quantum simulation and computing. A simple quantum photonic integrated circuit will be able to perform a second‐order auto‐correlation measurement and to demonstrate two‐photon interference of single photons that are generated, filtered, processed and detected on the very same chip. (Picture: Christof P. Dietrich et al., 10.1002/lpor.201500321 pp. 870–894, in this issue)